Performance of piezoelectric energy harvester with vortex-induced vibration and various bluff bodies - Adhes Gamayel; Mohamad Zaenudin; Brainvendra Widi Dionova (Universitas Ahmad Dahlan, 2023)
Piezoelectric energy harvesters (PEHs) are a kind of energy harvester that generates electricity due to pressure or vibration. Vortex-induced vibration (VIV) is a method that utilized wind energy and bluff body to generate the vibration in PEH. The objective of this research was to study the output voltage that generates in different bluff bodies with various airflow velocities. Experimental and simulation have done in this study. Experimental used PEH that consists of piezoelectric bimorph and rectangular-trapezoid fin. Bluff bodies with various cross-sectional areas, namely rhombus, square, and triangle were set up in front of the PEH at a distance of 80 cm. The various air velocities are set up to 5, 7, and 9 m/s in the wind tunnel with a cross-section of 250 mm × 250 mm. The simulation used the finite element method in explore the fluid flow pattern. The rhombus cross-sectional bluff body can generate voltage with an average of 1.5 volts. It is more voltage generated than a square and triangle. A vortex is formed near the rhombus bluff body and generates pressure fluctuation in its wake region. This pressure fluctuation takes place until airflow hits and leads PEH to vibrate and generate the voltage.